Patient understanding of the revised USPSTF screening mammogram guidelines: need for development of patient decision aids - Allen Summer V; Solberg Nes Lise; Marnach Mary L; Polga Kristen; Jenkins Sarah M; Files Julia A; Croghan Ivana T; Ghosh Karthik; Pruthi Sandhya (BMC, 2012)
Abstract Background The purpose of the study was to examine patients' understanding of the revised screening mammogram guidelines released by the United States Preventive Services Task Force (USPSTF) in 2009 addressing age at initiation and frequency of screening mammography. Methods Patients from the Departments of Family Medicine, Internal Medicine, and Obstetrics and Gynecology (n = 150) at a tertiary care medical center in the United States completed a survey regarding their understanding of the revised USPSTF guidelines following their release, within four to six months of their scheduled mammogram (March 2010 to May 2010). Results Of the patients surveyed, 97/147 (67%) indicated increased confusion regarding the age and frequency of screening mammography, 61/148 (41%) reported increased anxiety about mammograms, and 58/146 (40%) reported anxiety about their own health status following the release of the revised screening guidelines. Most of the patients surveyed, 111/148 (75%), did not expect to change their timing or frequency of screening mammograms in the future. Conclusion Results from this survey suggested increased confusion and possibly an increase in patients' anxiety related to screening mammography and their own health status following the release of the revised USPSTF screening mammogram guidelines to the public and subsequent media portrayal of the revised guidelines. Although the study did not specifically address causality for these findings, the results highlight the need for improvements in the communication of guidelines to patients and the public. Development of shared decision-making tools and outcomes should be considered to address the communication challenge.